The Effects of Education Level, Work Environment, and Work Motivation on Employee Productivity - Irzal Fathoni; Maya Novita Sari (Research Horizon, 2026)
In an increasingly volatile landscape, conventional human resource management models heavily favor formal sectors, creating a critical empirical shortage regarding inclusive, community-driven agricultural systems that support vulnerable groups. This study aims to examine and elucidate the isolated and simultaneous effects of education level, work motivation, and work environment on work productivity. Employing a quantitative associative design, this research conducted a census on a saturated sample of 30 active farmers, utilizing structured Likert-scale questionnaires alongside secondary institutional documentation for data collection. The data were analyzed through multiple linear regression diagnostics using IBM SPSS Statistics 23. The empirical results demonstrate that education level, work motivation, and work environment each exert a positive and statistically significant effect on work productivity, both partially and simultaneously. Notably, education level emerged as the most dominant individual predictor. Consequently, these findings imply that local stakeholders must prioritize adaptive vocational training modules, retrofit agricultural infrastructure to enhance physical accessibility, and strengthen communal psychological mentorship to foster sustainable economic self-reliance among disabled farmers.